Kresy bliskie i dalekie - Ostrowski, Jan K. (Krakow : Universitas, 1998)
A study of historic church buildings in the former lands of Eastern Poland, now in the Ukraine.
Keywords: Cities and towns -- Ukraine -- History; Church buildings -- Ukraine; Ukraine -- History, Local